Cellulase over lactic acid bacteria in enhancing antioxidant capacity of mulberry silage via phenolic release - Guo, Yaya; Peng, Hongmei; Wang, Hailiang; Li, Shu; Zhao, Jiantao; Zhang, Wenju (Frontiers in Microbiology, 2025)
Mulberry (Morus alba L.) is an economically valuable tree rich in phenolics, but its silage quality is limited by low epiphytic lactic acid bacteria (LAB) and water-soluble carbohydrate (WSC) content. This study evaluated the effects of adding epiphytic LAB and cellulase on the fermentation quality, bacterial community, metabolite composition, and antioxidant capacity of mulberry silage. A strain of Lactiplantibacillus plantarum LP26, with rapid acid production and high acid tolerance, was isolated and used as an inoculant. Four treatments were applied: untreated control (CK), LAB addition (LAB), cellulase addition (C), and their combination (C_LAB). The results showed that, compared with the CK group, the C and C_LAB groups significantly reduced pH and ammonia nitrogen content, increased lactic acid and WSC, and inhibited yeast and coliforms. They also decreased neutral detergent fiber (NDF), hemicellulose, and cellulose contents. Antioxidant assays showed notably higher DPPH and ABTS radical scavenging activities in the C and C_LAB groups. 16S rRNA sequencing revealed reduced bacterial diversity and increased Lactobacillus abundance (96.51%) and decrease Enterobacter abundance (5.12%) in C_LAB. Metabolomics analysis indicated that both C and C_LAB markedly altered phenylpropanoid and polyketide profiles, upregulating antioxidants like Camelliaside B and Quercetin 3-O-xylosyl-rutinoside, and enriching pathways such as flavonoid biosynthesis. In conclusion, cellulase enhanced antioxidant capacity by degrading fiber to release phenolics and improve fermentable substrates, while LAB alone had minimal effects. Although combining LAB and cellulase synergistically improved the microbial community, it did not provide additive benefits in phenolic conversion or antioxidant enhancement.